Giving - Hughes, Shirley, 1927- (Cambridge, Mass. : Candlewick Press, 1993)
A little girl and her baby brother experience the various aspects of giving, finding that it is nice whether you are giving a present, a smile, or a kiss.
"First published in Great Britain in 1993 by Walker Books Ltd., London."--page facing t.p.
1 13 17 18 26
Keywords: Generosity -- Fiction; Gifts -- Fiction; Gifts -- Juvenile fiction; Generosity -- Juvenile fiction